The Application of Game-Based Learning Model Accompanied by Wordwall on Students' Learning Independence in PAI BP Subject - Padila, Cisia; Asril, Zainal; Eliza, Rivdya; Remiswal, Remiswal; Fitriza, Rozi; Batubara, Juliana; Illahi, Rilci Kurnia (An-Nuha, 2025)
This study aims to determine the application of the Game Based Learning model accompanied by Wordwall media on student learning independence in Islamic Religious Education and Morality (PAI BP) subjects at SD Angkasa Padang. The background of this study is based on the low level of student learning independence in PAI BP learning, which tends to still depend on teachers. This study used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The research subjects were fifth-grade students at SD Angkasa Padang, who were divided into an experimental class and a control class. The research instruments were a learning independence questionnaire and an observation sheet of student learning activities. The data were analyzed using a t-test to see the significant difference between the two groups. The results showed that the implementation of the Game-Based Learning model with the help of Wordwall had a positive effect on increasing student learning independence. Students became more active, motivated, and able to manage their learning time independently. Thus, the implementation of the Game-Based Learning model accompanied by Wordwall can be used as an alternative effective learning strategy to increase student learning independence in PAI BP lessons in elementary schools.